Gel Electrophoresis for Investigating Enzymes with Biotechnological Application - Polizeli, Maria de Lourdes T. M.; Peixoto-Nogueira, Simone C.; Silva, Tony M. da; Maller, Alexandre; Cabral, Hamilton (IntechOpen, 2012)
None